Structural Modeling and in planta Complementation Studies Link Mutated Residues of the Medicago truncatula Nitrate Transporter NPF1.7 to Functionality in Root Nodules - Yu, Yao-Chuan; Dickstein, Rebecca; Longo, Antonella (Frontiers in Plant Science, 2021)
Symbiotic nitrogen fixation is a complex and regulated process that takes place in root nodules of legumes and allows legumes to grow in soils that lack nitrogen. Nitrogen is mostly acquired from the soil as nitrate and its level in the soil affects nodulation and nitrogen fixation. The mechanism(s) by which legumes modulate nitrate uptake to regulate nodule symbiosis remain unclear. In Medicago truncatula, the nitrate transporter MtNPF1.7 has been shown to control nodulation, symbiosis, and root architecture. MtNPF1.7 belongs to the nitrate/peptide transporter family and is a symporter with nitrate transport driven by proton(s). In this study we combined in silico structural predictions with in planta complementation of the severely defective mtnip-1 mutant plants to understand the role of a series of distinct amino acids in the transporter’s function. Our results support hypotheses about the functional importance of the ExxE(R/K) motif including an essential role for the first glutamic acid of the motif in proton(s) and possibly substrate transport. Results reveal that Motif A, a motif conserved among major facilitator transport (MFS) proteins, is essential for function. We hypothesize that it participates in intradomain packing of transmembrane helices and stabilizing one conformation during transport. Our results also question the existence of a putative TMH4-TMH10 salt bridge. These results are discussed in the context of potential nutrient transport functions for MtNPF1.7. Our findings add to the knowledge of the mechanism of alternative conformational changes as well as symport transport in NPFs and enhance our knowledge of the mechanisms for nitrate signaling.